Suicide among agricultural, forestry, and fishery workers: a systematic literature review and meta-analysis - Justine Klingelschmidt; Allison Milner; Imane Khireddine-Medouni; Katrina Witt; Evangelos C Alexopoulos; Susanna Toivanen; Anthony D LaMontagne; Jean-François Chastang; Isabelle Niedhammer (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This review aimed to quantify suicide risk among agricultural, forestry, and fishery workers and study potential variations of risk within this population. METHODS: We conducted a systematic literature review and meta-analysis from 1995 to 2016 using MEDLINE and following the PRISMA guidelines. A pooled effect size of suicide risk among the population of interest was calculated using meta-analysis. Subgroup analyses were conducted to investigate whether effect size differed according to population or study characteristics. Meta-regression was used to identify sources of heterogeneity. RESULTS: The systematic review identified 65 studies, of which 32 were included in the meta-analysis. Pooled effect size was 1.48 [95% confidence interval (CI) 1.30-1.68] representing an excess of suicide risk among the population of interest. Subgroup analysis showed that this effect size varied according to geographic area, with a higher effect size in Japan. The following study characteristics were found to contribute to the between-study variance: reference group, measure of effect size, and study design. CONCLUSIONS: Our findings suggest an excess of suicide risk among agricultural, forestry, and fishery workers and demonstrated that this excess may be even higher for these groups in Japan. This review highlights the need for suicide prevention policies focusing on this specific population of workers. More research is also needed to better understand the underlying factors that may increase suicide risk in this population.